Human collagen-based multifunctional composite material as well as preparation method and application thereof

Through the cross-linking network of four-arm polyethylene glycol-mercapto and alkenyl collagen and the combination of hyaluronic acid and Mg-HA nanoparticles, the problem of insufficient mechanical strength and controllability of natural collagen is solved, and the high strength and controllable degradation of multifunctional composite materials are achieved, which is suitable for biomedical materials.

CN120393127APending Publication Date: 2025-08-01SHENZHEN RUIMEI REGENERATIVE MEDICINE TECHNOLOGY DEVELOPMENT CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510668553.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-23
Publication Date
2025-08-01

AI Technical Summary

Technical Problem

The existing natural human collagen materials have shortcomings in mechanical strength, degradation controllability and functional integration, resulting in easy interface stratification, rapid degradation and functional conflicts after implantation.

Method used

Four-arm polyethylene glycol-mercapto (4ARM-PEG-SH) and alkened collagen are used to form a four-dimensional crosslinking network through click chemical reaction, combining hyaluronic acid and magnesium-doped hydroxyapatite (Mg-HA) nanoparticles to form a multi-layer spherical structure, and a bionic topological structure is formed by vacuum drying and ultraviolet crosslinking.

Benefits of technology

It significantly improves the tensile strength and degradation controllability of the material, promotes directed cell migration, and provides the basis for biomedical application of multifunctional composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120393127A_ABST
    Figure CN120393127A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a human collagen-based multifunctional composite material. Main raw materials of the composite material comprise four-arm polyethylene glycol-sulfydryl, alkenylated collagen, hyaluronic acid and magnesium-doped hydroxyapatite nanoparticles, and finally a multilayer sphere spatial configuration product is formed. The four-arm polyethylene glycol-sulfydryl is a star-shaped polymer, the center of the star-shaped polymer is of a four-arm structure connected by ethyoxyl, and the tail end of each arm is provided with sulfydryl. Through click chemical reaction of sulfydryl and alkenyl, the four-arm polyethylene glycol-sulfydryl serving as an internal framework can react with four pieces of alkenyl collagen at the same time to form four-way three-dimensional cross-linking, so that network compactness is achieved, and the tensile strength of the material can be greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of medical materials, and particularly to a human-derived collagen-based multifunctional composite material, its preparation method and application. Background Art

[0002] Collagen, as the most abundant structural protein in the human body (accounting for 70% - 80% of the dry weight of the dermis), is widely used in the field of tissue repair due to its excellent biocompatibility and cell adhesion promoting properties. However, the inherent defects of natural human-derived collagen make it difficult to meet the comprehensive clinical requirements for mechanical strength, controllable degradation, and functional integration. The specific technical bottlenecks are as follows: 1. Mechanical property imbalance: The initial modulus of pure collagen materials is lower than that of human bone tissue. For some existing reinforcement techniques, such as compounding certain materials with collagen, although the tensile strength of the resulting materials is improved, their fracture toughness is poor, which may lead to easy interfacial delamination after implantation. <{

[0003] 2. Degradation - regeneration asynchrony: The half-life of unmodified collagen under the action of various enzymes in the body is ≤7 days, which is much faster than the 21 - 28 days required for the wound repair cycle.

[0004] 3. Multifunctionality mutual exclusion problem: The interfacial incompatibility between the inorganic reinforcement phase (such as hydroxyapatite) and the collagen matrix leads to functional conflicts. For some techniques, compounding collagen with graphene makes the surface contact angle of the material larger, which will significantly inhibit the spreading of fibroblasts. Summary of the Invention

[0005] The purpose of the present invention is to disclose a preparation method and application of a human-derived collagen-based multifunctional composite material, so as to solve one or more technical problems existing in the prior art, and provide at least one beneficial choice or create conditions.

[0006] The first aspect of the present invention is to provide a collagen-based multifunctional composite material.

[0007] The second aspect of the present invention is to provide a preparation method of the composite material described in the first aspect of the present invention.

[0008] The third aspect of the present invention is to provide the use of the composite material described in the first aspect of the present invention.

[0009] The main raw materials of the composite material described in the first aspect of the present invention include four-armed polyethylene glycol-thiol (4ARM-PEG-SH), alkenylated collagen, hyaluronic acid, and magnesium-doped hydroxyapatite (Mg-HA) nanoparticles, and finally form a multi-layer spherical spatial configuration product. The 4ARM-PEG-SH is a star-shaped polymer with a four-armed structure connected by ethoxy groups at the center, and each arm end is equipped with a thiol group. Through the thiol-ene click chemical reaction between the thiol group and the alkenyl group, the 4ARM-PEG-SH serving as the internal skeleton can react with 4 alkenylated collagens simultaneously to form a four-way three-dimensional crosslinking, which has network denseness and can greatly improve the tensile strength of the material.

[0010] The preparation method described in the second aspect of the present invention includes the following steps: S1. Mix four-armed polyethylene glycol-thiol and alkenylated collagen, and carry out a thiol-ene click chemical reaction to obtain the product 4ARM-PEG-SH@collagen; S2. Mix the 4ARM-PEG-SH@collagen with hyaluronic acid, and carry out a Schiff base reaction to obtain OHA@4ARM-PEG-SH@collagen; S3. Mix Mg-HA nanoparticles with the OHA@4ARM-PEG-SH@collagen to obtain Mg-HA@OHA@4ARM-PEG-SH@collagen.

[0011] The preparation method first reacts the 4ARM-PEG-SH with the alkenylated collagen to form a four-dimensional three-dimensional network with a very high crosslinking density, which can greatly improve the tensile strength. Then the amino group of the alkenylated collagen reacts with hyaluronic acid to form a spherical structure with a hyaluronic acid layer on the outer layer of the four-dimensional three-dimensional network. Finally, the Mg-HA nanoparticles are evenly loaded in the sphere to make the spherical composite material more dense.

[0012] In a further application embodiment, the preparation method further includes the step: S4. Pour the Mg-HA@OHA@4ARM-PEG-SH@collagen into a mold and then carry out vacuum drying and ultraviolet crosslinking to form a biomimetic surface topological structure.

[0013] The purpose of step S4 is to form a biomimetic topological structure on the surface of the composite material through the micro-imprinting treatment of the mold, which helps to guide cell directional migration when the composite material is subsequently used as a medical material.

[0014] In a further application embodiment, the alkenylated collagen in step S1 is obtained by activating lysine residues of human-derived collagen under acidic conditions and then modifying it with an alkenylation reagent. Animal collagen may cause allergic reactions due to species differences and may carry pathogens. Human-derived collagen has almost no immunogenicity and higher safety. Acidic conditions can unwind human-derived collagen into a single-chain form, exposing the ε-amino group (-NH2) of lysine, and then directly adding an alkenylation reagent to covalently link allyl groups to human-derived collagen through nucleophilic substitution reaction of the amino group.

[0015] In a further application embodiment, the acidic conditions refer to stirring in a 0.5 mol / L acetic acid solution (pH = 3.0) for 24 hours.

[0016] In a further application embodiment, after treatment with acetic acid In a further application embodiment, the alkenylation reagent is selected from N-hydroxysuccinimide-allyl ester (NHS-Alloc), vinylboronic acid pinacol ester, or vinyltrimethoxysilane. In a further preferred application embodiment, the dosage of the alkenylation reagent is 50 - 200 wt% of the human-derived collagen. Taking NHS-Alloc as an example, the acidified collagen also needs to react with NHS-Alloc at pH = 7.4 for 2 - 10 hours.

[0017] In a further application embodiment, the molecular weight of the tetra-arm polyethylene glycol-thiol in step S1 is 1000 - 10000. In a further preferred application embodiment, the molecular weight of the tetra-arm polyethylene glycol-thiol is 4000 - 6000.

[0018] In a further application embodiment, the reaction conditions for the click chemical reaction in step S1 are 37 ± 1 °C, pH = 7.4, under nitrogen protection, and the reaction time is 1 - 5 hours; preferably, the reaction time is 1 - 3 hours.

[0019] In a further application embodiment, the hyaluronic acid in step S2 is subjected to oxidation treatment before use, and the aldehyde group content after treatment is 5 - 50%. In a further preferred application embodiment, the aldehyde group content of the hyaluronic acid after treatment is 10 - 20%; in an even more preferred application embodiment, the aldehyde group content of the hyaluronic acid after treatment is 14 - 16%.

[0020] In a further application embodiment, the oxidation treatment of the hyaluronic acid is carried out in a sodium periodate (NaIO) solution with a concentration of 0.01 - 0.5 mol / L, preferably a concentration of 0.09 - 0.2 mol / L; the reaction time is 1 - 10 hours, preferably 3 - 5 hours.

[0021] In a further application embodiment, the addition amount of the oxidized hyaluronic acid is 5-20% of the mass of the alkenylated collagen; the further preferably used amount is 8-12%.

[0022] In a further application embodiment, the Mg-HA nanoparticles described in step S3 are first ultrasonically activated with a 0.1 mol / L citric acid solution for 10-60 minutes.

[0023] In a further application embodiment, the Ca / Mg ratio of the activated Mg-HA nanoparticles is (1-20):1. In a further preferably application embodiment, the Ca / Mg ratio is (8-10):1.

[0024] In a further application embodiment, the particle size of the Mg-HA nanoparticles is 20-80 nm. In a further preferably application embodiment, the particle size of the Mg-HA nanoparticles is 45-55 nm.

[0025] In a further application embodiment, the mass fraction of the Mg-HA nanoparticles is 1-50%. The preferably mass fraction is 5-15%.

[0026] In a further application embodiment, in step S3, a high-pressure homogenizer is used under a pressure condition of 5-30 MPa and circulated 5-10 times to ensure that the Mg-HA nanoparticles are evenly distributed in a gradient manner in the composite material.

[0027] In a further application embodiment, the inner wall surface of the mold in step S4 is provided with groove textures for helping to form a bionic surface topological structure. The width of the grooves is 10-30 μm, the depth is 1-20 μm, and the spacing is 10-50 μm.

[0028] In a further application embodiment, the mold is a polydimethylsiloxane (PDMS) component.

[0029] In a further application embodiment, the condition parameters for pouring in step S4 are: pressure 0.1-1.0 MPa, preferably 0.6-0.7 MPa; temperature 30-60 °C, preferably 44-46 °C; time 5-20 minutes, preferably 14-16 minutes.

[0030] In a further application embodiment, the condition parameters for vacuum drying in step S4 are: -80 to -40 °C, preferably -55 to -45 °C; time is 12-48 hours, preferably 23-25 hours.

[0031] In a further application embodiment, the ultraviolet alternating current in step S4 refers to crosslinking under ultraviolet light of 360 - 368 nm for 1 - 20 minutes, preferably 4 - 8 minutes.

[0032] The application described in the third aspect of the present invention is based on the fact that the collagen - based multifunctional composite material can exhibit good performance when used as a drug - controlled release carrier, a bone repair scaffold, or artificial skin. The covalent bond provided by click chemistry can provide lasting mechanical support, and the non - covalent bond provided by the Schiff base reaction can regulate the degradation rate. The two donors constitute the basis for the collagen - based multifunctional composite material to be used as a biomedical material. The surface ζ potential of Mg - HA nanoparticles can enhance the electrostatic adsorption with collagen. The subsequent steps of casting, vacuum drying, and ultraviolet crosslinking endow the collagen - based multifunctional composite material with a biomimetic surface topology composed of micro - grooves, which can promote cell spreading. Description of the Drawings

[0033] Figure 1 SEM image of collagen; Figure 2 SEM image of human - derived collagen after treatment with 4ARM - PEG - SH and hyaluronic acid; Figure 3 SEM image of human - derived collagen after homogenization treatment with Mg - HA nanoparticles. Detailed Embodiments

[0034] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the spirit and essence of the present invention, modifications and substitutions made to the methods, steps, or conditions of the present invention all fall within the scope of the present invention.

[0035] Unless otherwise specified, the technical means used in the examples are conventional means well - known to those skilled in the art.

[0036] The measurement or evaluation of the characteristic values recorded in this specification is carried out according to the following methods.

[0037] Tensile strength: After cutting samples according to ASTM D638 - Type IV standard (thickness 0.5 ± 0.05 mm), equilibrating for 48 hours at a temperature of 23℃ and a relative humidity of 50%, testing with an Instron 5966 universal testing machine, loading rate 5 mm / minute, gauge length 50 mm, execution standard: ASTM D638 - 14.

[0038] Compressive strength: Tested with a Zwick Z050, load range 0 - 50 kN, strain rate 0.5% / s, execution standard: ISO604.

[0039] Cell viability: Tested using a BioTek Synergy H1 microplate reader, excitation wavelength 450 nm, reference wavelength 650 nm. Test method: ISO 10993-5 CCK-8 method.

[0040] Nanoparticle size: Observed using a Malvern Zetasizer Nano ZS, scattering angle 173°, temperature 25°C ± 0.1°C.

[0041] Surface morphology: Observed using a Hitachi SU8010 field emission electron microscope, acceleration voltage 5 kV, working distance 8 mm.

[0042] In vitro degradation: In a PBS solution containing 1 mg / mL collagenase, using a thermostatic shaker (TS-211B), oscillating at 60 rpm at 37 ± 0.5°C.

[0043] Drug sustained release: In a PBS buffer at pH = 7.4, using a dialysis bag (MWCO, 10 kDa), sampling at intervals of 0 / 1 / 3 / 7 / 14 / 21 / 28 days.

[0044] Drug loading efficiency: Tested using an Agilent HPLC 1260 high performance liquid chromatograph.

[0045] Chromatographic column: Agilent ZORBAX SB-C18 (4.6×250 mm, 5 μm).

[0046] Mobile phase A: 0.1% aqueous TFA solution. Mobile phase B: Acetonitrile (gradient elution).

[0047] Flow rate: 1.0 mL / minute.

[0048] Wavelength: 280 nm.

[0049] Column temperature: 30°C.

[0050] Scanning electron microscope (SEM) image: Imaged using a Hitachi SU8010 field emission electron microscope. The sample was cryosectioned with a thickness of 10 μm and sputter-coated with a 5 nm Au layer, acceleration voltage 5 kV.

[0051] Example 1, Preparation of an artificial skin repair material using a human-derived collagen-based multifunctional composite material Step (1): Oxidize 100 g of hyaluronic acid in a 0.1 mol / L NalO solution until the aldehyde group content reaches 15%.

[0052] Step (2): Activate Mg-HA nanoparticles with a Ca / Mg ratio of 9:1 and a particle size of 50 ± 5 nm by ultrasonic treatment in 0.1 mol / L citric acid solution for 30 minutes.

[0053] Step (3): Stir 600 g of human-derived collagen in 0.5 mol / L acetic acid solution (pH = 3.0) for 24 hours. Then, in a phosphate buffer solution at 37 ± 1°C and pH = 7.4, add 1000 g of NHS-Alloc and stir for 2 hours. Under nitrogen protection, mix and react with 50 g of 4ARM-PEG-SH with a molecular weight of 5000 for 2 hours. Then add 100 g of oxidized hyaluronic acid and mix and react for 2 hours. Subsequently, add 150 g of activated Mg-HA nanoparticles and cycle 5 times at 15 MPa with a high-pressure homogenizer to obtain a composite material.

[0054] Step (4): Pour the composite material into a PDMS mold and shape it at 0.5 MPa and 45°C. The inner wall surface of the mold is provided with parallel grooves with a width of 20 ± 2 μm, a depth of 5 μm, and a spacing of 30 μm.

[0055] Figure 1 Is human-derived collagen without any treatment, with an irregular network structure. Figure 2 Is human-derived collagen after treatment with 4ARM-PEG-SH and hyaluronic acid. It can be observed that its original network pore size significantly decreases, forming a relatively uniform pore structure, indicating that 4ARM-PEG-SH and hyaluronic acid grow in the four-dimensional network direction based on human-derived collagen. Figure 3 Is human-derived collagen further homogenized with Mg-HA nanoparticles. It can be seen that after filling with Mg-HA nanoparticles, the material structure is more compact and the porosity becomes smaller.

[0056] Test the obtained artificial skin repair materials respectively. The measured tensile strength is 28.9 ± 8 MPa; the elongation at break is 160 ± 7%; the in vitro degradation period is 48 days. Test the cell viability of L929 fibroblasts (culture conditions: DMEM + 10% FBS, 37°C, 5% CO2) for 72 hours, and the measured cell activity is 97.8 ± 0.7%.

[0057] Example 2: Preparation of a bone repair scaffold from a human-derived collagen-based multifunctional composite material Steps (1) to (3) are the same as in Example 1.

[0058] Step (4): Pour the composite material into a PDMS mold and set it at 0.5 MPa and 45°C. The set composite material is frozen at -20°C for 24 hours and then freeze-dried to form an interconnected pore structure with a pore size of 100 - 200 μm. The porosity is measured to be 85 ± 3% by mercury intrusion method. Subsequently, it is irradiated with a UV lamp with a wavelength of 365 nm at 10 mW / cm 2 for 5 minutes for crosslinking.

[0059] The obtained bone repair scaffolds are tested respectively. The measured tensile strength is 45.7 ± 2.1 MPa; the elongation at break is 120 ± 5%; the in vitro degradation period is 56 days. The cell viability of MC3T3-E1 osteoblasts is tested for 72 hours, and the cell activity is measured to be 95.2 ± 1.2%.

[0060] Example 3, Preparation of a Drug Sustained Release Carrier from a Human-derived Collagen-based Multifunctional Composite Material Take the bone repair scaffold prepared in Example 2 for drug loading to determine its drug loading and release rate.

[0061] The composite material with a porosity of 85 ± 3% and a pore size of 100 - 200 μm after setting treatment is sterilized by γ-ray irradiation at 25 kGy, and then immersed in a 10 μg / mL recombinant human vascular endothelial growth factor (rhVEGF) HCl solution (4 mmol / L, containing 0.1% BSA), and 10 mmol / L trehalose is added as a stabilizer, and then kept at a pressure of -0.08 MPa for 30 minutes. Then the pressure is released to atmospheric pressure, and the cycle is repeated 3 times to complete drug fixation.

[0062] Use a UV lamp with a wavelength of 365 nm, at a distance of 15 cm, and an intensity of 10 mW / cm 2 for 5 minutes for crosslinking, and then pre-freeze with a 5% mannitol solution, freeze at -80°C for 24 hours and then freeze-dry.

[0063] The drug loading is measured to be 1.5 μg / mg by UV spectrophotometry, and the drug loading efficiency is 92.3 ± 3.1% (detected by HPLC, drug loading efficiency = (CoVo - CrVr) / m scaffold × 100%, Co: initial concentration, Cr: residual concentration, V: solution volume). The measured tensile strength is 12.3 ± 0.5 MPa; the elongation at break is 180 ± 9%, and the in vitro degradation period is 42 days. The above drug-loaded scaffold is used for the culture of human umbilical vein endothelial cells (HUVEC, ATCC CRL-1730) (EGM-2 (Lonza CC-3162) containing 2% FBS, 37°C, 5% CO2), and the cell activity is observed to be 93.7 ± 1.5% after 72 hours, and the drug release rate at 28 days is 82.7 ± 4.2%.

[0064] For those skilled in the art, it is obvious that the present invention is not limited to the details of the above-described exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the present invention. Therefore, from any point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the appended claims rather than the above description. Therefore, all changes falling within the meaning and scope of the equivalent elements of the claims are intended to be embraced within the present invention.

Claims

1. A method for preparing a composite material, characterized in that, Including the steps: S1. Mix tetra-arm polyethylene glycol-thiol with vinylated collagen and carry out thiol-ene click chemical reaction to obtain the product 4ARM-PEG-SH@collagen; S2. Mix the 4ARM-PEG-SH@collagen with hyaluronic acid and carry out Schiff base reaction to obtain OHA@4ARM-PEG-SH@collagen; S3. Mix magnesium-doped hydroxyapatite nanoparticles with the OHA@4ARM-PEG-SH@collagen to obtain Mg-HA@OHA@4ARM-PEG-SH@collagen.

2. The preparation method according to claim 1, characterized in that, It also includes the step: S4. Pour the Mg-HA@OHA@4ARM-PEG-SH@collagen into a mold and then carry out vacuum drying and ultraviolet cross-linking to form a biomimetic surface topology structure.

3. The preparation method according to claim 1 or 2, characterized in that, In step S1, the vinylated collagen is obtained by activating lysine residues of human-derived collagen under acidic conditions and then modifying with a vinylating reagent.

4. The preparation method according to claim 3, characterized in that, The vinylating reagent is selected from N-hydroxysuccinimide-allyl ester, vinylboronic acid pinacol ester or vinyltrimethoxysilane; preferably, the dosage of the vinylating reagent is 50-200 wt% of the human-derived collagen.

5. The preparation method according to claim 1 or 2, characterized in that In step S1, the molecular weight of the tetra-arm polyethylene glycol-thiol is 1000-10000; preferably, the molecular weight of the tetra-arm polyethylene glycol-thiol is 4000-6000.

6. The preparation method according to claim 1 or 2, characterized in that, The conditions of the click chemical reaction in step S1 are: 37±1 °C, pH value 7.4, 1-5 hours.

7. The preparation method according to claim 1 or 2, characterized in that, The hyaluronic acid in step S2 is subjected to oxidation treatment before use, and the aldehyde group content is 5-50%; preferably, the aldehyde group content is 10-20%; more preferably, the aldehyde group content is 14-16%.

8. According to the preparation method described in claim 1 or 2, characterized in that In step S3, the Ca / Mg ratio of the magnesium-doped hydroxyapatite nanoparticles is (1-20):1; preferably, the Ca / Mg ratio is (8-10):1; preferably, the particle size of the magnesium-doped hydroxyapatite nanoparticles is 20-80 nm.

9. A collagen-based multifunctional composite material, characterized in that, Prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the collagen-based multifunctional composite material according to claim 9 in the preparation of a drug sustained-release carrier, a bone repair scaffold or artificial skin.